From Species to Regional and Local Specialization of Intestinal Macrophages - Arroyo Portilla, Cynthia; Tomas, Julie; Gorvel, Jean-Pierre; Lelouard, Hugues (Frontiers in Cell and Developmental Biology, 2021)
Initially intended for nutrient uptake, phagocytosis represents a central mechanism of debris removal and host defense against invading pathogens through the entire animal kingdom. In vertebrates but also many invertebrates, macrophages (MF) and MF-like cells (e.g. coelomocytes and hemocytes) are professional phagocytic cells that seed tissues to maintain homeostasis through pathogen killing, efferocytosis and tissue shaping, repair and remodeling. Some MF functions are common to all species and tissues whereas others are specific to their homing tissue. Indeed, shaped by their microenvironment, MF become adapted to perform particular functions, highlighting their great plasticity and giving rise to high population diversity. Interestingly, the gut displays several anatomic and functional compartments with large pools of strikingly diversified MF populations. This review focuses on recent advances on intestinal MF in several species, which have allowed to infer their specificity and functions.